A taxonomic revision of the genus Daedalma Hewitson with the descriptions of twenty new taxa and the immature stages of two species (Lepidoptera: Nymphalidae: Satyrinae) - Pyrcz, Tomasz W.; Greeney, Harold F.; Willmott, Keith R.; Wojtusiak, Janusz (Zootaxa, 2011)
The taxonomy of the Andean butterfly genus Daedalma (Nymphalidae, Satyrinae) is discussed. Generic synapomorphies based on adult morphology are proposed, and the relationships with allied genera of the subtribe Pronophilina are evaluated. The status of Junea as the sister-genus of Daedalma is reconsidered, particularly in light of new data on the larval stages. The genus Daedalma is divided into two presumed monophyletic groups distinguished by a series of morphological and ecological characters. Three species, D. eliza n. sp., D. dognini n. sp. and D. rubroreducta n. sp., and seventeen new subspecies are described, one new status is proposed, and three lectotypes are designated. Female genitalia of Daedalma are described for the first time and their taxonomical value is assessed. The early stages of D. rubroreducta and D.dinias are described, the first larval descriptions for any species of Daedalma. Distribution and diversity patterns of Daedalma are discussed. Distribution maps, illustrations of male and female genitalia, and figures of adult butterflies of both sexes are provided for all taxa where possible, with comments on bionomics and adult behaviour for all taxa in the genus.